eTrace / Nurfaizah Kamarudin ... [et al.] - Kamarudin, Nurfaizah; Md Saleh, Mohd Nor Azam; Mohsin, Mohsinin; Kassim, Nor Hayati; Halamy, Suhaida (Universiti Teknologi MARA, Kedah, 2019)
eTrace is a navigation app which is used by a smartphone and created to solve the problem for new students or visitors who have a difficulty in finding the places in UiTM Samarahan, Sarawak campus during their first visit. It is very useful in locating the specific locations in Universiti Teknologi MARA Sarawak, such as the student affairs department, academic affairs department, bursary, facilities management department and others. eTrace has uniqueness especially in using the navigation apps in finding the places in Universiti Teknologi MARA Samarahan, Sarawak campus. Thus, it will make the users fully utilized and familiar with the campus layout during their first visit. Furthermore, it will save the time and energy for the users in finding the places in UiTM Samarahan, Sarawak. Besides, it will make the users become more familiar with the campus layout. eTrace has the setting features to support the users in terms of searching button, adjusting the brightness and magnifying options. Based on the usefulness and features of eTrace, it can be applied and practically used by all campuses of Universiti Teknologi MARA as well as other institutions that needed the specific location-to-go. Apart from that, eTrace can play an important role as a navigation tool in assisting the users to find the direction of each places precisely and effectively.